Top management team faultlines and corporate industrial diversification: The mediating role of strategic attentional breadth - Chen, Weihong; Chen, Chen; Xiong, Xiaoguo (Frontiers in Psychology, 2023)
Integrating faultline theory and the attention-based view, this paper explores the impact and process mechanisms of two types of faultlines (i.e., task-related faultlines and relationship-related faultlines) within top management teams (TMTs), specifically on corporate industrial diversification. Based on the empirical evidence of Chinese A-share non-financial listed firms from 2008-2021, this paper obtains the following research findings: first, task-related TMT faultlines promote corporate industrial diversification, while conversely, relationship-related TMT faultlines inhibit corporate industrial diversification. Second, task-related TMT faultlines promote firms’ strategic attentional breadth, while conversely, relationship-related TMT faultlines inhibit firms’ strategic attentional breadth. Third, strategic attentional breadth plays a partially-mediating role in the relationship between both types of TMT faultlines and firms' industrial diversification. This study extends the research related to corporate industrial diversification based on micro-level explanatory mechanisms, and also provides implications and guidance for the rational allocation of TMT and firms’ industrial diversification management practices.